Penentuan Acid Value Dan Saponification Value Wax Ester Pada Section 110 Di PT X - Syafrinal Syafrinal; Muhammad Luthfian Chandra (Politeknik ATI Padang, 2020)
This study aims to determine the Acid Value (AV) and the Saponification Value (SV) of Wax ester for each reactor in section 110 and compare the values obtained with the PT X standard. The method used is alkalimetry to determine the acid value and acidimetry for the determination of the Saponification Value. The results obtained were Acid Value 0.92 ppm - 1.02 ppm which was following the PT X standard, max 1ppm. The Saponification Value the results obtained were 132 ppm - 142 ppm which was following the PT X standard, min 130 ppm. This indicates that the resulting wax ester can be used for the preparation of fatty alcohols in sections 111-113.